Range Finding Test of Scirpus Grossus on Aluminium and Iron Contaminated Soil - Anindita Sari Pertiwi; Ipung Fitri Purwanti; Bieby Voijant Tangahu; Setyo Budi Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
High concentration metal in soil may cause pollution. Particularly for aluminium and iron in soil. Even though these substances are necessary micro-substances for plants, but if the soil has it in high concentration, it will cause more complex environmental problem. These two metals were found in high concentration in soil near the small Industry Environment that recycled aluminium in Jombang Regency, East Java. High concentration also caused soil contamination, thus treatment towards the land was needed. One of the best solutions to overcome land contamination was phytoremediation. Scirpus grossus, to date, is the most widely used wild plant which has the ability in remediating metal pollutant in soil. Before treating metal on soil, toxicity test needed to be done beforehand. Toxicity test was done using Range Finding Test (RFT) method for 7 days using reactors with each filled with 5 kg of soil and 4 plants. RFT was done in different concentration composition between Al:Fe. The load variation (mg/kg) of Al:Fe in the reactors were 10.000:0, 5.000:50, 500:500, 50:5.000, 0:10.000 and control reactor. The result obtained after 7 days were that Scirpus grossus plant could survive in pollution load of Al:Fe 500:500 (mg/kg) with 75% percentage of living plants.